ANALISIS PENERAPAN ENTERPRISE ARCHITECTURE DALAM INVESTASI PENGELOLAAN TEKNOLOGI INFORMASI - Sandy Kosasi (SISFOTENIKA, 2013)
Abstracts: The fact that occurs in the application of EA is apparently not as easy or smooth as expected or under exposure of the concepts EA theory itself. Information technology decisions that are not built from a series of precise analysis, fundamental, and in accordance with the specification requirements will guide the organization to the conditions paradox of information technology. Planning still partial in which only focused on specific business processes, lack of flexibility, appropriate planning, portfolio management, work measurement, and processes needed to manage information technology expenditure. Many organizations simply look at EA as a collection of a number of business applications and software are needed at this time and not as an essential framework to support business strategy. The failure of the application of EA is also not uncommon to be caused by problems in non-technical areas such as leadership, communication and change management skills. The focus of the EA should be able to provide value to organizational growth, change organizational culture, performance and productivity of every business process, and can execute a broader organizational strategy according to the model of the application of EA in the organization.Keywords : Enterprise Architecture (EA), Business-IT Alignment framework, Paradox of Information Technology, and non-technical areas.